Inhibition of Monoacylglycerol Lipase Prevents Chronic Traumatic Encephalopathy-like Neuropathology in a Mouse Model of Repetitive Mild Closed Head Injury. Issue 3 (March 2015) - Zhang, Jian; Teng, Zhaoqian; Song, Yunping; Hu, Mei; Chen, Chu
Emerging evidence suggests that the risk of developing chronic traumatic encephalopathy (CTE), a progressive neurodegenerative disease, is significantly increased in military personnel and contact sports players who have been exposed to repetitive trauma brain injury (TBI). Unfortunately there are no effective medications currently available for prevention and treatment of CTE. Here we demonstrate that inhibition of monoacylglycerol lipase (MAGL), the key enzyme that metabolizes the endocannabinoid 2-arachidonoylglycerol (2-AG) in the brain, significantly reduced CTE-like neuropathologic changes in a mouse model of repetitive mild closed head injury (rmCHI). Inhibition of 2-AG metabolism promoted neurologic recovery following rmCHI and reduced proinflammatory cytokines, astroglial reactivity, expression of amyloid precursor protein and the enzymes that make Aβ, as well as formation of Aβ. Importantly, neurodegeneration, TDP-43 protein aggregation, and tau phosphorylation, which are the neuropathologic hallmarks of CTE, were significantly suppressed by MAGL inactivation. Furthermore, alterations in expression of glutamate receptor subunits and impairments in basal synaptic transmission, long-term synaptic plasticity, and spatial learning and memory were recovered by inhibition of 2-AG metabolism in animals exposed to rmCHI. Our results suggest that MAGL inhibition, which boosts 2-AG and reduces 2-AG metabolites prostaglandins in the brain, may lead to a new therapy for CTE.